Unconventional N-H…N Hydrogen Bonds Involving Proline Backbone Nitrogen in Protein Structures - Deepak, R. N. V. Krishna (Biophys J, 2016)
Contrary to DNA double-helical structures, hydrogen bonds (H-bonds) involving nitrogen as the acceptor are not common in protein structures. We systematically searched N-H…N H-bonds in two different sets of protein structures. Data set I consists of neutron diffraction and ultrahigh-resolution x-ray structures (0.9 Å resolution or better) and the hydrogen atom positions in these structures were determined experimentally. Data set II contains structures determined using x-ray diffraction (resolution ≤ 1.8 Å) and the positions of hydrogen atoms were generated using a computational method. We identified 114 and 14,347 potential N-H…N H-bonds from these two data sets, respectively, and 56–66% of these were of the N(i+1)-H(i+1)…N(i) type, with N(i) being the proline backbone nitrogen. To further understand the nature of such unusual contacts, we performed quantum chemical calculations on the model compound N-acetyl-L-proline-N-methylamide (Ace-Pro-NMe) with coordinates taken from the experimentally determined structures. A potential energy profile generated by varying the ψ dihedral angle in Ace-Pro-NMe indicates that the conformation with the N-H…N H-bond is the most stable. An analysis of H-bond-forming proline residues reveals that more than 30% of the proline carbonyl groups are also involved in n → π(∗) interactions with the carbonyl carbon of the preceding residue. Natural bond orbital analyses demonstrate that the strength of N-H…N H-bonds is less than half of that observed for a conventional H-bond. This study clearly establishes the H-bonding capability of proline nitrogen and its prevalence in protein structures. We found many proteins with multiple instances of H-bond-forming prolines. With more than 15% of all proline residues participating in N-H…N H-bonds, we suggest a new, to our knowledge, structural role for proline in providing stability to loops and capping regions of secondary structures in proteins.